A fungal effector inhibits plant MAPK signaling by acting as a decoy substrate of MKK5 - Xiu-qi Liu; Xian-ping Liu; Lin Jin; Min Luo; Yu-jia Tang; Yu-zhuo Yan; Cheng-Guo Duan; Chen Zhu (Proceedings of the National Academy of Sciences, 2026)
Plant immune responses rely on mitogen-activated protein kinase (MAPK) cascade that integrates pattern-triggered immunity and effector-triggered immunity. How fungal pathogens suppress this central signaling hub remains poorly understood. Here, we identify a secreted effector from phytopathogenic fungus Verticillium dahliae , VdHCE1, that is required for full virulence and directly targets host MAPK signaling. VdHCE1 interacts with the MAPK kinase MKK5 and is phosphorylated at threonine 166 in planta. Biochemical analyses demonstrated that VdHCE1 competes with MPK3 and MPK6 as a substrate of MKK5, thereby attenuating downstream MAPK activation. Consistently, VdHCE1 suppresses elicitor- and NLR-triggered immune responses, while deletion of VdHCE1 compromises fungal virulence in Arabidopsis and cotton. Genetic disruption of MKK5 restores the virulence of VdHCE1-deficient strains, establishing MKK5 as the functional target of VdHCE1. These findings reveal a strategy by which a filamentous fungal pathogen suppresses plant immunity by acting as a decoy substrate within the MAPK cascade and provide a molecular framework for engineering resistance to vascular wilt disease.